PERILAKU PENANGANAN EMESIS GRAVIDARUM PADA IBU HAMIL TM 1 DI BPM NY. MUSRIFAH AMD.KEB DUSUN KAUMAN DESA BANGSAL KEC. BANGSAL KAB. MOJOKERTO TAHUN 2015 - Puji Suryantini, Naning; Mila, Chuzaimatul (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Pregnancy was not an event that is experienced, in the early days of its development, one common complaint was Emesis gravidarum occurs around 65-70%. Emesis gravidarum vomiting light, but did not interfere with daily activities. This study was to investigated the behavior of the handling of emesis gravidarum in TM 1 pregnant women in BPM Mrs. Musrifah Amd.Keb. Kauman Village Bangsal district Mojokerto 2014. The design study used descriptive methods. The population was all TM 1 pregnant women experiencing emesis gravidarum at BPM Mrs. Musrifah Amd.Keb. Kauman Village Bangsal district Mojokerto. The sample was 21 respondents drawn using sampling. Researchers collectting data used primary data obtained directly from respondents through a questionnaire. Analysis of the data used T scores and presented in a frequency distribution table. The result showed behavioral treatment of emesis gravidarum in pregnant women TM 1 is mostly negative as many as 12 respondents (57.1%). Many forms of negative behavior such as mothers do rarely eat foods with balanced nutrition such as carbohydrates from rice, protein from fish or meat, vitamins from fruits, rarely drink water with sufficient quantities, rarely taking any medications that have been prescribed by a doctor or midwife . Midwives in place research should implement the function as executor by always provide midwifery care that is appropriate for the treatment of emesis gravidarum. In addition it should improve the functioning of education by education pregnant women ways to handle emesis gravidarum.Keywords: Behavior, Emesis Gravidarum, TM 1 pregnant women